ASSESSMENT OF RESIDENCE SANITATION CONDITION AND LIFE QUALITY OF CONSTRUCTION WORKERS, CHONBURI PROVINCE, THAILAND - Danai Bawornkiattikul; Nantaporn Phatrabuddha (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Thailand economic has grown for last decade in all enterprise. Especially, construction is one industry composed by various important factors such as technology finance worker and etc. Workers in construction industry are the human resources that need welfare to promote life quality of workers. One of important welfare is the residence during constructing. Camps or residence need good sanitary management for supporting for supporting life quality of worker. Aim of this study was to assess sanitation condition of residence and life quality of construction workers.Methodology: To survey residence sanitation, Questionnaire for life quality in 3 aspects, for samples of workers in 3 camps A B C of 3 construction sites, Analyze and compare data by as percentage and criteria that provided as 4 level of sanitation condition and life quality.Results: Camp A sanitation was 78.70% indicating the residence sanitation was in good level meanwhile 3 aspects of life quality were during 67.45 - 70.53 % defining that samples lived and worked full effective. Camp B was 62.50 % indicating fair level of sanitation meanwhile life quality were during 63.83 - 66.89 %. Camp C was 66.00 % indicating same camp B, meanwhile life quality ranged during 63.83 - 66.89 % that same Camp A and B. Conclusion Good sanitation management of residence influence good life quality of worker. This study could be used as tool and evidence to evaluate not only sanitation condition and life quality, these also could be used to test the consistent of both.